2021
DOI: 10.1039/d1cp02958d
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced Raman scattering in ETPTA inverse photonic crystals with gold nanoparticles

Abstract: We present a substrate design for surface-enhanced Raman scattering by decorating three-dimensional inverse photonic crystals with a small amount of Au nanoparticles. Photonic crystals with different positions of the photonic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Ashurov et al. (2021) found that the enhancement factor (EF) and the PBG are closely related when the pigment is used for detection. When the excitation wavelength coincides with the PBG, a strong enhancement effect will be produced, which can reach 1–2 × 10 5 .…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ashurov et al. (2021) found that the enhancement factor (EF) and the PBG are closely related when the pigment is used for detection. When the excitation wavelength coincides with the PBG, a strong enhancement effect will be produced, which can reach 1–2 × 10 5 .…”
Section: Applicationsmentioning
confidence: 99%
“…In addition, the slow photon effect of PCs can enhance light absorption by adjusting the photon path (J. I. L. Chen et al, 2008;Jovic et al, 2016; X.-G. . Ashurov et al (2021) found that the enhancement factor (EF) and the PBG are closely related when the pigment is used for detection. When the excitation wavelength coincides with the PBG, a strong enhancement effect will be produced, which can reach 1-2 × 10 5 .…”
Section: Raman Spectrummentioning
confidence: 99%
“…At the same time, synthetic opals and inverse opals are very promising materials for producing substrates for surface enhanced Raman scattering (SERS). [19][20][21][22][23][24] Micropatterned polymerized materials have been used for creating microenvironments to manipulate and allow controlled growth of cells. [25] Moreover, micropatterned polymeric materials containing PhC matrix can offer various advantages including ready addressability, productivity and multiplexing capability for a range of applications including protein patterning, [26] enzyme detection, [27] and high-sensitivity humidity sensing.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, synthetic opals and inverse opals are very promising materials for producing substrates for surface enhanced Raman scattering (SERS). [ 19–24 ]…”
Section: Introductionmentioning
confidence: 99%